2016
DOI: 10.5465/amr.2014.0073
|View full text |Cite
|
Sign up to set email alerts
|

Problematizing Fit and Survival: Transforming the Law of Requisite Variety Through Complexity Misalignment

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 196 publications
(215 reference statements)
1
35
0
Order By: Relevance
“…Ligthart et al (2016) found that time pressure disabled flexibility. Agency plays a crucial role in the complexity (Poulis & Poulis, 2016) of dynamic projectsthat is, project teams play a role in staging their own issues. Figure 2 depicts how the project team was able to solve a wide range of issues in a dynamically complex project by the use of five processes.…”
Section: Modeling a Pattern Of Intelligent Processesmentioning
confidence: 99%
“…Ligthart et al (2016) found that time pressure disabled flexibility. Agency plays a crucial role in the complexity (Poulis & Poulis, 2016) of dynamic projectsthat is, project teams play a role in staging their own issues. Figure 2 depicts how the project team was able to solve a wide range of issues in a dynamically complex project by the use of five processes.…”
Section: Modeling a Pattern Of Intelligent Processesmentioning
confidence: 99%
“…However, despite the pervasiveness of this recommendation, many firms are unsuccessful in responding to disruption (Christensen et al, ; Fuentelsaz et al, ; King and Baatartogtokh, ; Uzunca, ) raising the question of the validity, feasibility, or boundaries of such an internal fit perspective. The universality of the strategic alignment perspective has recently been challenged by the idea that consistency can become less viable when firms face diverse contingencies and conflicting requirements (Le Breton‐Miller and Miller, ; Poulis and Poulis, ; Smith, ). In this opposing perspective, it is argued that organizations are able to thrive by embracing misalignment between internal components (Gulati and Puranam, ) and promoting inconsistent mentalities and structures (Smith et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we add to the recent debates over whether internal alignment has a universal value as a lever for effective strategic change (Le Breton‐Miller and Miller, ; Poulis and Poulis, ; Smith et al, ). In particular, we propose market heterogeneity as a potential a boundary condition for whether focusing on internal fit may constitute an effective response to disruption.…”
Section: Introductionmentioning
confidence: 99%
“…seePoulis & Poulis, 2016 for a critique).The whole discussion of fit in IB is infused with assumptions of voluntary judgment and unilateral action by cognitively acute managers. Though these assumptions create the necessary parsimony for theorizing, they are unrealistic in the-unanimously acknowledged as complex-IB environment.…”
mentioning
confidence: 99%